Peran Badan Nasional Pencarian dan Pertolongan (Basarnas) dalam Mendukung Strategi Pertahanan Nasional di Wilayah Maritim Indonesia (Studi Kasus: Perbatasan Laut Selat Malaka) - I Nyoman Parwata; Syamsul Maarif; Pujo Widodo; Helda Risman (LPPM Institut Pendidikan Nusantara Global, 2026)
As the largest archipelagic country, Indonesia faces complex challenges in maintaining maritime security. Basarnas, as the search and rescue (SAR) agency, plays a crucial role in supporting national defense, especially in addressing non-military threats such as maritime accidents and natural disasters (Frishfelds et al., 2023). This study uses a qualitative approach and case study method to explore Basarnas' contribution to Indonesia's maritime defense strategy. The results show that Basarnas plays a significant role in responding to maritime incidents, enhancing inter-agency coordination, and strengthening safety in Indonesian waters. Synergy with the Navy (TNI AL) is also key to preparedness against both military and non-military maritime threats. In conclusion, Basarnas not only engages in rescue efforts but also strengthens the nation's defense in maritime areas. Strengthening Basarnas' operational capacity and closer collaboration with defense components are necessary to achieve sustainable maritime security.